Cord blood graft composition impacts the clinical outcome of allogeneic stem cell transplantation. Issue 2 (24th January 2014) - Wikell, H.; Ponandai‐Srinivasan, S.; Mattsson, J.; Gertow, J.; Uhlin, M.
Abstract Introduction Despite routine use of umbilical cord blood (CB) grafts as stem cell source for allogeneic stem cell transplantations, much remains unknown regarding their cell composition and correlation with clinical outcome. Methods We analyzed material from 30 CB units used for allogeneic hematopoietic stem cell transplantation by multicolor flow cytometry. Phenotypic data were correlated with various clinical outcomes such as survival, graft‐versus‐host disease (GVHD), relapse, rejection, viral reactivation, and bacteremia. Results We found that above‐median frequencies of CD69+ T cells, naïve CD8+ T cells, and CD127+ B cells in the CB graft were each associated with significantly improved patient survival. Moreover, a statistically significant correlation was seen between higher levels of CD94+ T cells and herpes simplex virus and varicella zoster virus reactivation post transplantation. A similar correlation was seen for the frequency of CD95+ cells in total CD3+, as well as CD4+ and CD8+ T‐cell subsets, and viral reactivation. Finally, a higher frequency of naïve CD8+ T cells was associated with the incidence of acute GVHD. Conclusion Our study highlights the importance of further exploration of graft composition before CB transplantation as a tool for risk prediction.